La révolution automobile - Bardou, Jean-Pierre; Chanaron, Jean-Jacques; Fridensen, Patrick; Laux, James M. (Paris : Albin Michel, 1977)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: auto-industrie